A new n-type polymer based on N, N′-dialkoxynaphthalenediimide (NDIO) for organic thin-film transistors and all-polymer solar cells. Issue 6 (29th January 2018) - He, Yinghui; Li, Xu; Liu, Haitao; Meng, Han; Wang, Guan Ying; Cui, Bo; Wang, Jinliang; Li, Yuning
Abstract : A novel electron acceptor building block, N, N ′-dialkoxynaphthalenediimide (NDIO), is synthesized and used to develop an n-type polymer semiconductor. Abstract : The electron acceptor building block N, N ′-dialkoxynaphthalenediimide (NDIO) has been, for the first time, used to develop an n-type polymer semiconductor, P(NDIO2OD-T). The polymer exhibits unipolar electron charge transport with an electron mobility of up to 5.4 × 10 −3 cm 2 V −1 s −1 in organic thin-film transistors (OTFTs) and shows good air-stability. When it is used as the acceptor in all-polymer solar cells (all-PSCs), a PCE of up to 3.25% is achieved. The performances of the OTFTs and all-PSCs based on this polymer have improved compared to its N, N ′-dialkyl-substituted analogue.